Structural and magnetic properties of Fe and Ni co-doped SnO2 nanoparticles prepared by co-precipitation method - Mst Halima Khatun; Ruhul Amin; Md Samiul Islam Sarker; Md Rasel Shikder; Suravi Islam; Md Shahjahan (Materials Research Express, 2024)
In this research work Fe and Ni co-doped Tin oxide (SnO _2 ) nanoparticles have been prepared by co-precipitation method. The samples were prepared at various combination of Fe and Ni from 0% up to 10%. The produced nanoparticles were studied by x-ray diffraction (XRD), Scanning Electron Microscopy (SEM), UV–vis Spectrophotometer, Fourier Transformation Infrared Spectroscopy (FTIR) and Vibrating Sample Magnetometer (VSM). The XRD study reveals the formation of rutile structure of the undoped and doped SnO _2 nanoparticles with the average crystallite size of 1.5–10.8 nm. Metal oxide bonding is confirmed through FTIR measurement. Optical band gap redshift (3.9 to 3.64 eV) with doping of Fe and Ni atom is observed. SEM image confirms the formation of spheroidal nanoparticles and size of the nanoparticle varies from 36 to 15 nm. The VSM study shows the ferromagnetic phase transition at 7% Ni, Fe doped SnO _2 nanoparticles. This ferromagnetism arises for the oxygen vacancies and defect states. Further, increase of doping concentration of 10%, nanoparticles show the phase transition from ferromagnetic to paramagnetic. Such transition can be applicable in hyperthermia treatment and memory devices.